Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Exercise 8.3

Show that [tex]\( u(x, y) = x \sqrt{xy} \)[/tex] satisfies the equation
[tex]\[
x u_x - y u_y = u
\][/tex]
subject to
[tex]\[
u(y, y) = y^2, \quad y \geq 0.
\][/tex]


Sagot :

To show that the function [tex]\( u(x, y) = x \sqrt{x y} \)[/tex] satisfies the equation [tex]\( x u_x - y u_y = u \)[/tex] subject to [tex]\( u(y, y) = y^2 \)[/tex] for [tex]\( y \geq 0 \)[/tex], we will go through several steps.

### Step 1: Compute the partial derivatives of [tex]\( u \)[/tex]

First, let's find the partial derivatives of [tex]\( u \)[/tex] with respect to [tex]\( x \)[/tex] and [tex]\( y \)[/tex].

1. Partial derivative with respect to [tex]\( x \)[/tex]:
[tex]\[ u_x = \frac{\partial}{\partial x} \left( x \sqrt{x y} \right) \][/tex]
To differentiate, we use the product rule:
[tex]\[ u_x = \frac{\partial}{\partial x} \left( x (xy)^{1/2} \right) \][/tex]
Let [tex]\( f(x) = x \)[/tex] and [tex]\( g(x) = (xy)^{1/2} \)[/tex]:
[tex]\[ u_x = f'(x) g(x) + f(x) g'(x) \][/tex]
[tex]\[ f'(x) = 1 \quad \text{and} \quad g'(x) = \frac{1}{2} (xy)^{-1/2} \cdot y = \frac{y}{2 \sqrt{xy}} \][/tex]
[tex]\[ u_x = 1 \cdot (xy)^{1/2} + x \cdot \frac{y}{2 \sqrt{xy}} \][/tex]
[tex]\[ = \sqrt{xy} + \frac{x y}{2 \sqrt{xy}} \][/tex]
[tex]\[ = \sqrt{xy} + \frac{x y}{2 \sqrt{xy}} = \sqrt{xy} + \frac{1}{2} \sqrt{xy} \][/tex]
[tex]\[ = \frac{3}{2} \sqrt{xy} \][/tex]

2. Partial derivative with respect to [tex]\( y \)[/tex]:
[tex]\[ u_y = \frac{\partial}{\partial y} \left( x \sqrt{x y} \right) \][/tex]
To differentiate, we use the chain rule:
[tex]\[ u_y = x \cdot \frac{\partial}{\partial y} \left( (xy)^{1/2} \right) \][/tex]
[tex]\[ = x \cdot \frac{1}{2} (xy)^{-1/2} \cdot x \][/tex]
[tex]\[ = x \cdot \frac{x}{2 \sqrt{xy}} \][/tex]
[tex]\[ = \frac{x^2}{2 \sqrt{xy}} \][/tex]
[tex]\[ = \frac{x \sqrt{xy}}{2y} \][/tex]

Thus, we have:
[tex]\[ u_x = \frac{3 \sqrt{xy}}{2} \][/tex]
[tex]\[ u_y = \frac{x \sqrt{xy}}{2y} \][/tex]

### Step 2: Verify the given equation [tex]\( x u_x - y u_y = u \)[/tex]

Next, we need to plug these partial derivatives into [tex]\( x u_x - y u_y \)[/tex] and verify if it equals [tex]\( u \)[/tex].

Substitute [tex]\( u_x \)[/tex] and [tex]\( u_y \)[/tex]:
[tex]\[ x u_x - y u_y = x \left(\frac{3 \sqrt{xy}}{2}\right) - y \left(\frac{x \sqrt{xy}}{2y}\right) \][/tex]
[tex]\[ = \frac{3 x \sqrt{xy}}{2} - \frac{x \sqrt{xy}}{2} \][/tex]
[tex]\[ = \frac{3 x \sqrt{xy} - x \sqrt{xy}}{2} \][/tex]
[tex]\[ = \frac{2 x \sqrt{xy}}{2} \][/tex]
[tex]\[ = x \sqrt{xy} \][/tex]

Since [tex]\( u(x, y) = x \sqrt{x y} \)[/tex], we have shown:
[tex]\[ x u_x - y u_y = u \][/tex]

### Step 3: Check the specific case [tex]\( u(y, y) = y^2 \)[/tex] for [tex]\( y \geq 0 \)[/tex]

Now, we need to verify the condition [tex]\( u(y, y) = y^2 \)[/tex].

Substitute [tex]\( x = y \)[/tex] into [tex]\( u \)[/tex]:
[tex]\[ u(y, y) = y \sqrt{y \cdot y} \][/tex]
[tex]\[ = y \sqrt{y^2} \][/tex]
[tex]\[ = y \cdot y \][/tex]
[tex]\[ = y^2 \][/tex]

As [tex]\( u(y, y) = y^2 \)[/tex] is indeed satisfied for [tex]\( y \geq 0 \)[/tex], the given condition holds.

### Conclusion

We have verified that [tex]\( u(x, y) = x \sqrt{x y} \)[/tex] satisfies both the differential equation [tex]\( x u_x - y u_y = u \)[/tex] and the condition [tex]\( u(y, y) = y^2 \)[/tex] for [tex]\( y \geq 0 \)[/tex].